INVENTARISASI KEANEKARAGAMAN ANGGREK (Orchidaceae) DI HUTAN RESORT WAY KANAN BALAI AMAN NASIONAL WAY KAMBAS SEBAGAI SUMBER INFORMASI DALAM MELESTARIKAN PLASMA NUTFAH - Hening Widowati, Dwi Agustin (Bioedukasi Jurnal Pendidikan Biologi, 2015)
Abstract: Orchid is one of the plants that have different characteristics in each species and its habitat. Orchids (Orchidaceae) or nation is a group that is protected by Government Regulations Number. 7 Th.1999. It is necessary to look at the type of data collections and save it, and look at the characteristics of tropical forests in the Resort Way Kanan. This research aims to inventory orchid the found in Forest Resort of Way Kanan. This research was conducted in December 2014 until January 2015, using purposive sampling method and using techniques Line transeck, cut the line following the path of the Post traking Right Way to the SRS (Sumatran Rhino Sanctuary), in this research using 4 stations between stations within 2km. The results of this study were obtained 23 species of orchids with 9 genera and 14 species include: the genus Dendrobium, Dendrobium creatceum, Dendrobium crumenatum, genus Grammatophyllum, Grammatophyllum scriptum BL, Agrostophyllum genus, the genus Cymbidium, Cymbidium chloranthum, Cymbidium hartinahianum, Calanthe genus, the genus Bulbophyllum, Arachnis sp, Angraecum didieri, Ascocentrum miniatum, Ascocentrum aureum, Coelogyne foerstermanni, golden shower Oncidium, Phalaenopsis amabilis, Spathoglottis sp. Having analyzed the data obtained it has a value equal to 46% of species density and relative density of 88.36% with a diversity index value of 1.3, based on the criteria of the Shannon-Wienner in Fachrul abundant species diversity can be expressed with the criteria being. The results of this study compiled into resources in conserving germplasm in the form of books and banner summary information, because there are some orchids are found in Forest Resort Way Kanan Balai Way Kambas National Park in Government Regulations Number. 7 Th.1999 is a protected species of orchids. Orchid is a protected plant species, therefore it is necessary for us to maintain and preserve it.